2015
DOI: 10.3945/jn.114.202176
|View full text |Cite
|
Sign up to set email alerts
|

Increased Whole Grain Consumption Does Not Affect Blood Biochemistry, Body Composition, or Gut Microbiology in Healthy, Low-Habitual Whole Grain Consumers

Abstract: A combination of dietary advice and provision of commercially available food items enabled subjects with a low-moderate habitual consumption of WG to substantially increase their WG intake, but there was little effect on blood biochemical markers, body composition, BP, fecal measurements, or gut microbiology. This trial was registered at www.controlled-trials.com as ISRCTN36521837.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 49 publications
8
66
2
Order By: Relevance
“…Moreover, the magnitude of the effect was estimated to be greater than that attributed to the nondigestible energy content of the fiber itself. The between-group differences in fiber intake and stool weight equated to a difference of 4 g stool/g fiber, which was consistent with recent reports on the relation between stool weight and cereal fiber intake (10,46). Likewise, the increase in the stool energy content within the WG was consistent with multiple reports that have collectively shown that increasing dietary fiber intake reduces dietary energy digestibility (47,48).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Moreover, the magnitude of the effect was estimated to be greater than that attributed to the nondigestible energy content of the fiber itself. The between-group differences in fiber intake and stool weight equated to a difference of 4 g stool/g fiber, which was consistent with recent reports on the relation between stool weight and cereal fiber intake (10,46). Likewise, the increase in the stool energy content within the WG was consistent with multiple reports that have collectively shown that increasing dietary fiber intake reduces dietary energy digestibility (47,48).…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, these results provide new mechanistic insights that support the consistent inverse associations between whole-grain intake and BMI and adiposity that have been documented in epidemiologic studies (3-9), but which have been largely unsubstantiated in previous clinical trials (4,(10)(11)(12)(13)(14)(15)(16)(17). As such, this study adds support for dietary guidance recommending the consumption of whole grains in place of refined grains.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations